Questioning the Role of Forward Associative Strength in False Memories: Evidence From Deese-Roediger-McDermott Lists With Three Critical Lures - Beato, Maria Soledad; Arndt, Jason (Frontiers in Psychology, 2021)
We report an experiment examining the factors that produce false recognition in the Deese-Roediger-McDermott (DRM) paradigm. We selectively manipulated the probability that critical lures produce study items in free association, known as forward associative strength (FAS), while controlling the probability that study items produce critical lures in free association, known as backward associative strength (BAS). Results showed that false recognition of critical lures failed to differ between strong and weak FAS conditions. Follow-up correlational analyses further supported this outcome, showing that FAS was not correlated with false recognition, despite substantial variability in both variables across our stimulus sets. However, these correlational analyses did produce a significant and strong relationship between BAS and false recognition. These results support views that propose false memory is produced by activation spreading from study items to critical lures during encoding, which leads critical lures to be confused with episodically-experienced events.